Social transfers in rural China: Do they contribute to poverty reduction? - Lena Kuhn; Stephan Brosig; Linxiu Zhang (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
In order to combat absolute poverty in rural China, the “Rural Minimum Living Standard System” was launched nationally in 2007. The program provides direct monetary transfers to rural households living below the poverty line. A recent research project working with a sample of around 5000 households found that monetary transfers were being misallocated to a considerable extent, which greatly reduced the effectiveness of the program: 89 percent of the recipient households were not eligible according to their (reported) income while 79 percent of households assessed to be eligible according to their reported income were unable to receive the necessary assistance. Qualitative investigations revealed that these misallocations were often caused by a lack of human resources among local administrations within structurally weak regions. Additional financial aid provided by the central government towards the cost of the program's implementation could lead to considerable improvement in targeting, i.e. the identification of households eligible to receive transfers. However, due to an inability to accurately measure and document income, the implementation of a closely supervised system such as those found in central Europe does not appear to be suitable in the near future. In the mid-term, a step by step replacement of social transfers with health and pension benefits should be discussed in order to alleviate the high administrative cost engendered by targeting based on income. – – Zur Bekämpfung absoluter Armut im ländlichen China wurde 2007 landesweit das "Rural Minimum Living Standard System" eingeführt, welches direkte finanzielle Unterstützung für ländliche Haushalte unterhalb der Armutsgrenze vorsieht. Im Rahmen eines jüngeren Forschungsprojektes wurden in einer Stichprobe von knapp 5000 Haushalten extreme Fehlzuweisungen von Transfermitteln festgestellt, welche die Wirksamkeit des Programmes stark reduzierten: Während 89 Prozent der Empfängerhaushalte nach Ergebnissen dieser Studie gar nicht unterhalb der Armutslinie lagen, konnten etwa 79 Prozent der absolut armen Haushalte nicht berücksichtigt werden. Wie qualitative Nachforschungen ergaben, lag die Ursache dieser Fehlverteilung oft in der mangelnden personellen Ausstattung lokaler Verwaltungen in strukturschwachen Regionen. Durch zusätzliche finanzielle Unterstützung der Zentralregierung bei den Implementierungskosten des Programmes könnte die Zielgenauigkeit des Programmes deutlich verbessert werden. Die Implementierung eines Systems so engmaschiger Kontrollen, wie etwa in mitteleuropäischen Systemen, ist jedoch aufgrund fehlender Einkommensdokumentation in näherer Zukunft kaum möglich. Mittelfristig sollte mit Blick auf den erheblichen administrativen Aufwand für bedarfsgerechte Sozialhilfevergabe ein stufenweiser Ersatz von Sozialtransfers durch Kranken- und Pensionsversicherung diskutiert werden.
urn:nbn:de:gbv:3:2-68387
Keywords: 330